Sudigai (Agnikarma) treatment for foot corn: Case report - Sritharan, G.; Anpuchelvi, S. (University of Colombo, Sri Lanka, 2023)
Suddigai (Agnikarma) means the procedure done with fire. References about Suddigai are available in almost all Siddha and Ayurvedic preventive, curative and haemostatic properties were unveiled even centuries back. These same principles are adopted in advanced technologies like cauterization, diathermy, radiation therapy, laser therapy, station device etc. Suddigai is the prime para-surgical procedure to treat chronic diseases, which are most difficult to manage because of the antagonistic property of doshas, like the disease caused by Kapha. Suddigai is done in neurogenic pain, tendinopathies or in diseases of skin, muscle, vein, ligament, bone or joint where the pain is an exclusive factor. A 64 years old male patient was admitted at Herbal Health Care Centre on 10th April 2017 with complaints of pain and elevated cystic swelling on the right and left sole due to rough and hard footwear. There was no history of direct trauma except that the patient was used to walking barefoot on rough roads. There was a history of excision of elevated layers of corn done repeatedly by the patient himself before visiting us. On the basis of clinical examinations, the patient was diagnosed as a case of corn at the right and left sole. After careful assessment and examination, the patient was treated with Sudigai. The Patient completely recovered from foot corns after regular use of Sudigai every week. Thus, from the case report it is clear that the Para-surgical procedure of Agnikarma / Sudigai helps to treat foot corns. So, Agnikarma therapy is more satisfactory in the management of corns
Keywords: Suddigai; Agnikarma; Siddha; Ayurveda; Kapha